Dukungan Sosial Teman Sebaya dengan Kesehatan Jiwa Remaja - Mauliza, Rizky; Harkensia, Linur Steffi; Ardianti, Riski Dian; Sabil, Teungku Muhammad; Drissianti, Putri (Journal of Telenursing (JOTING), 2025)
This study aims to determine the relationship between peer social support and adolescents' mental health at SMP Negeri 1 Syamtalira Bayu. The research method used a quantitative design with a cross-sectional approach. The results of this study indicate that 85.1% (189 respondents) reported good peer social support, 75.2% (167 respondents) reported normal mental health, and 66.7% (148 respondents) reported good peer social support. The relationship between peer social support and adolescents' mental health at SMP Negeri 1 Syamtalira Bayu was significant, with a p-value of 0.000. Conclusion: There is an essential relationship between peer social support and adolescents' mental health.   Keywords: Social Support, Peers, Mental Health, Adolescents